A Survey of Workforce Distribution, Workload, and Performance Outcomes of Doctorally-prepared Nurse Faculty Members in Nursing Institutions in Thailand - Vachprasit, Ratjai; Ppetpichetchian, Wongchan; Wannasuntad, Supaporn; Matchim, Yaowarat; Sitthimongkol, Yajai (Journal of Thailand Nursing and Midwifery Council, 2021)
Objective: To conduct a macro-perspective survey of workforce distribution, workload, and professional performance outcomes of doctorally-prepared nurse faculty (DNF) members in three major groups of nursing institutions in Thailand: 1) research-oriented universities; 2) the Nursing College of Praboromarajchanok Institute; and 3) other nursing institutions Design: Survey study Methodology: Survey questionnaires were mailed to all nursing institutions in Thailand (N = 88) to enquire about workforce distribution and the number of DNF members. Subsequently, another set of questionnaires was sent to each of the DNF members to enquire about work types, workload, and professional performance outcomes. In total, responses from 313 respondents were used for data analysis. The qualitative part of this study was conducted via in-depth interviews with 28 DNF members. Results: In total, there were 1,046 DNF members working in nursing educational institutions (24.5% of the entire number of nursing instructors). Research-oriented universities had the highest ratio of DNF members (53.4%), followed by other nursing institutions (19.6%) and the Nursing College of Praboromarajchanok Institute (16.8%). In terms of workload, no significant differences in researching and practicum teaching were found between the three groups of institutions. These institutions displayed a similarly high degree of emphasis on practicum teaching. However, there was significant difference of degrees of emphasis on administrative and other teaching responsibilities. In the past three years, the respondents from the three groups of institutions produced a total of 1,295 pieces of academic work, averagely one piece per person per year. The professional performance outcomes of each group was not significantly different. Internal factors (personal motivations) and external factors (institutional policies) were identified as significant factors in the respondents’ production of research studies, whilst lack of time and heavy workload were identified as major obstacles. Recommendations: It is advisable that nursing leaders at all levels provide DNF members with professional support and assistance to promote good performance outcomes.